INTERNATIONAL STUDENTS MOBILITY PROGRAM: EXPERIENCES OF INDONESIAN STUDENTS - Muhammad Patria Nebukadnedzar; Evi Karlina Ambarwati; Yuna Tresna Wahyuna (IKIP Siliwangi, 2022)
Learning is an activity that can be done anywhere and at any time as long as we have the desire to learn. Many people now travel abroad solely to learn. In this experience, exchange student found challenging on the cultural difference. This study aim to investigated Indonesian students' experience during the student mobility program abroad. Narrative inquiry was implemented to explore the experiences of two students by utilizing oral narratives by means of semi-structured interviews. The findings revealed that Indonesian students find it challenging talk to middle-aged people. In conclusion, perceive the challenges of living in other countries positively. Keywords: Challenges, Experience, Student Mobility, English Language